1995
DOI: 10.1002/j.1460-2075.1995.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

The receptor tyrosine kinase TIE is required for integrity and survival of vascular endothelial cells.

Abstract: Vascular endothelial cells are critical for the development and function of the mammalian circulatory system. We have analyzed the role of the endothelial cell‐specific receptor tyrosine kinase TIE in the mouse vasculature. Mouse embryos homozygous for a disrupted Tie allele developed severe edema, their microvasculature was ruptured and they died between days 13.5 and 14.5 of gestation. The major blood vessels of the homozygous embryos appeared normal. Cells lacking a functional Tie gene were unable to contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
278
2
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(299 citation statements)
references
References 25 publications
11
278
2
8
Order By: Relevance
“…On average, 6 to 8 fields were taken from each section. Results were expressed as mean number of vWF-positive vessels per mm 2 .…”
Section: The Matrigel Plug Assay To Assess In Vivo Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…On average, 6 to 8 fields were taken from each section. Results were expressed as mean number of vWF-positive vessels per mm 2 .…”
Section: The Matrigel Plug Assay To Assess In Vivo Angiogenesismentioning
confidence: 99%
“…1 Tie2 signaling has been shown to be required for later stages of embryonic blood vessel development, [2][3][4] including vascular remodeling, vessel integrity, and maturation. 1,5 In vitro experiments have shown that Ang1 induces endothelial cell (EC) sprouting in vitro, 6,7 and stimulates EC migration 8 and the formation and stabilization of capillary-like networks in culture systems.…”
mentioning
confidence: 99%
“…Targeted null mutations in all of these receptors result in embryonic lethality (Shalaby et al, 1995;Fong et al, 1995;Dumont et al, in prep. ;Dumont et al, 1994;Sato et al, 1995;Puri et al, 1995), and the lethal phenotype is distinct for each receptor. These results suggest that the signaling pathways that are mediated by these receptors play unique roles in development.…”
Section: Introductionmentioning
confidence: 99%
“…Tie-1 and tie-2 deficient mice die at later times than VEGF receptor null mice, exhibiting phenotypical alterations consistent with a role in vascular remodeling. 21,23,24 Ang-1 and Ang-2 are secreted glycoproteins that share ϳ60% amino acid identity and bind with similar affinity to tie-2. Although Ang-1 induces autophosphorylation of tie-2, Ang-2 is a naturally occurring antagonist that blocks Ang-1-induced tie-2 autophosphorylation.…”
mentioning
confidence: 99%